Bretherick's handbook of reactive chemical hazards : an indexed guide to published data. - Urben, P. G. (Academic, 2007)
Brethericks Handbook of Reactive Chemical Hazards is widely regarded as the reference work in this field an assembly of all reported risks such as explosion, fire, toxic or high-energy events that result from chemical reactions gone astray, with extensive referencing to the primary literature. It is designed to improve safety in laboratories that perform chemical synthesis and general research, as well as chemical manufacturing plants. Entries are ordered by empirical formula and indexed under both name(s) and Chemical Abstracts Registry Numbers. This two-volume compendium focuses on reactivity risks of chemicals, alone and in combination; toxicity hazards are only included for unexpected reactions giving volatile poisons. The 2-volume set is available on an introductory price of $320/270/185 until Jan 2007. Will then revert to the list price of $395/330/230. Order your copy at the introductory price now. * Predict, avoid, and control reactivity danger with this latest edition of the leading guide * Covers every chemical with documented information on reactive hazards; more than 5,000 entries on single elements or compounds, and 5,000 entries on the interactions between two or more compounds * Includes five years of new reports, new references to the primary literature, and amplification to existing entries * Links similar compounds or incidents that are not obviously related.